A Large Data Exchange Method for Multi-agent in Java Agent Development Framework - Wathiq Laftah Al-Yaseen; Zulaiha Ali Othman; Mohd Zakree Ahmad Nazri (International Review of Management and Marketing, 2016)
One of the Business Intelligent solutions that are currently in use is the Multi-Agent System (MAS). Communication is one of the most important elements in MAS, especially for exchanging large low level data between distributed agents (physically). The Agent Communication Language in JADE has been offered as a secure method for sending data, whereby the data is defined as an object. However, the object cannot be used to send data to another agent in a different machine. Therefore, the aim of this paper was to propose a method for the exchange of large low level data as an object by creating a proxy agent known as a Delivery Agent, which temporarily imitates the Receiver Agent. The results showed that the proposed method is able to send large-sized data. The experiments were conducted using 16 datasets ranging from 100,000 to 7 million instances. However, for the proposed method, the RAM and the CPU machine had to be slightly increased for the Receiver Agent, but the latency time was not significantly different compared to the use of the Java Socket method (non-agent and less secure). With such results, it was concluded that the proposed method can be used to securely send large data between agents. Keywords: Data Exchange, Multi-agent, Agent Communication, Low Level Data, Java Agent Development Framework JEL Classifications: C61, C63, C82, C88